(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to studying some widespread worldview stereotypes of People’s Commissariat of Internal Affairs (PCIA) officials during “Great Terror” in 1937-1938s. Typical Chekist image and his worldview focus is shown. Conclusion is made that the image was constituent of state Party officials and population consciousness manipulation policy in 1930s.